STUDY OF THE SPREAD OF G-308A POLYMORPHISM OF THE TNF-α GENE IN THE DEVELOPMENT OF CHRONIC GLOMERULONEPHRITIS IN THE UZBEK POPULATION (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Chronic glomerulonephritis (CGN) is a complex immunoinflammatory disease of the renal glomeruli, which develops in the body with prolonged inflammation, autoimmune reactions, and the participation of a number of genetic factors. Since CGN does not show clinical signs for a long time and can only be detected through laboratory tests, it belongs to the category of "silent" diseases. However, over time, it leads to a progressive decrease in kidney function, and as a result, to chronic renal failure. Currently, CGN is in the center of special attention as the main cause of renal failure. Thanks to research in the field of molecular genetics in recent еars, it has been established that genetic factors, in particular, the polymorphism of some genes, play an important role in the pathogenesis of CGN. In particular, the TNF-α gene (tumor necrosis factor alpha) plays an important role in the inflammatory and immune response.